Study on increasing load capacity of wooden arch bridge by CFRP strengthening: experimental and numerical Verification - Li, Liping; Wang, Yan; Zhang, Yafei; Wang, Xu; Ji, Guangyao; Li, Xuping (Frontiers in Materials, 2024)
The wooden arch corridor bridge is a typical representative of Chinese wooden bridges, holding significant historical research value. Currently, these bridges face issues of severe component deformation and insufficient load-bearing capacity. To address these problems, this study employs CFRP reinforcement on the components of wooden arch corridor bridges to reduce deformation and enhance load-bearing capacity. Experimental research on CFRP reinforcement has yielded the elastic modulus of the bonding interface. Given the lack of an accurate numerical model for wooden arch corridor bridges, this study establishes a precise numerical model by setting parameters based on load test data from wooden arch corridor bridges. The elastic modulus obtained from the experiments is input into the numerical model for analysis. The results indicate that CFRP exhibits excellent reinforcement performance, with the load-bearing capacity of the reinforced damaged components still reaching 75% to 85% of their original capacity, while the load-bearing capacity of the reinforced undamaged components increases to 130% to 140% of their original capacity. The failure modes of the CFRP-reinforced wooden components suggest that allowing for some gaps in the bonding of CFRP can enhance overall ductility. The application of CFRP to wooden arch corridor bridges also demonstrates favorable reinforcement effects, increasing the load-bearing capacity of the arch surface by approximately 20%, thereby providing a theoretical basis for the reinforcement of wooden arch bridge frameworks.